استقلال الرقابة الشرعية على المصارف الإسلامية الأردنية: الواقع والمأمول - البدارين، عبدالله محمد خلف; بركات، عماد رفيق خالد (جامعة آل البيت, 2019)
هدف البحث إلى بيان متطلبات الارتقاء باستقلال الرقابة الشرعية على المصارف الإسلامية في الأردن، وذلك من خلال دراسة واقع استقلال الرقابة الشرعية على تلك المصارف ،ثم اقتراح وسائل تسهم في رفع مستوى تلك الاستقلالية فيها، وقد توصل البحث إلى وجود متطلبات لاستقلال الرقابة الشرعية تتعلق بالتشريع، والاستقلال الإداري والتنظيمي والمالي والفكري، وأن هذه المتطلبات ينقصها الكثير في حالة الأردن؛ لذلك قدم البحث مقترحا لإنشاء هيئة رقابة شرعية مركزية تتمتع باستقلال مالي وإداري، تقوم بالرقابة الشرعية على عمل المصارف الإسلامية في الأردن، بما يؤدي إلى الارتقاء بمستوى استقلال الرقابة الشرعية، وتجاوز كل الانتقادات الموجهة لاستقلالها. وقد أوصت الدراسة بالاهتمام بهذا المقترح، وإجراء دراسات تبحث إمكانية التحسين والتطبيق.
The study aimed at clarifying the requirements for improving the independence of Shari'a supervision over Islamic banks in Jordan, studying the reality of the independence of Shari'a supervision over Islamic banks in Jordan, and suggesting means that contribute to raising the level of independence in this country. The study found that there are requirements for the independence of the Shari'a supervision relating to legislation, administrative, financial and intellectual independence, and that these requirements lack much in the case of Jordan, Therefore, the research proposed to establish a central Shari'a Supervisory Board with financial and administrative autonomy that would legally supervise the work of Islamic banks in Jordan, which would lead to the improvement of the level of independence of Shari'a supervision and overcome all criticisms of its independence. The study recommended that this proposal be taken into account, and studies should be conducted to examine the possibility of improvement and application.
Keywords: الرقابة الشرعية -- المصارف الإسلامية -- الاستقلال المؤسسى -- الاحكام الشرعية -- الأردن